2017
DOI: 10.3389/fnhum.2017.00348
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Profiles in HIV-Exposed, Uninfected and HIV-Infected Children: A Comparison with Neurotypical Controls

Abstract: This study compared the working memory profiles of three groups of children, namely HIV-infected (HIV-I; n = 95), HIV-exposed, uninfected (HIV-EU; n = 86) and an HIV-unexposed, uninfected, (HIV-UU; n = 92) neurotypical control group. Working memory, an executive function, plays an important role in frontal lobe-controlled behaviors, such as motivation, planning, decision making, and social interaction, and is a strong predictor of academic success in school children. Memory impairments have been identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 117 publications
(201 reference statements)
1
18
0
Order By: Relevance
“…Consistent with the findings of a study conducted among HIV-infected children on treatment in India, neurocognitive impairment was observed despite being on ART treatment for more than 2 years with an undetectable viral load and normal CD4 + cell count (23). Similar findings were found in a South African study that reported HIV-infected children with a median age of 5 years did not show improvement in neurocognitive function after 6 months of ART (24). In addition, the finding from the present study is consistent with studies showing that children infected with HIV relative to uninfected groups evidence focal neurocognitive deficits on task that measures working memory (25); processing speed (26); visual motor integration, sustained attention (27); and motor speed coordination (28).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the findings of a study conducted among HIV-infected children on treatment in India, neurocognitive impairment was observed despite being on ART treatment for more than 2 years with an undetectable viral load and normal CD4 + cell count (23). Similar findings were found in a South African study that reported HIV-infected children with a median age of 5 years did not show improvement in neurocognitive function after 6 months of ART (24). In addition, the finding from the present study is consistent with studies showing that children infected with HIV relative to uninfected groups evidence focal neurocognitive deficits on task that measures working memory (25); processing speed (26); visual motor integration, sustained attention (27); and motor speed coordination (28).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, studies of school-aged HEU children demonstrate subtle deficits compared to control children, particularly in language-related cognitive performance ( Van Rie et al, 2008 ; Kerr et al, 2014 ; Milligan and Cockcroft, 2017 ). A recent longitudinal study reported that neurodevelopment of HEU children is initially similar to their HIV-unexposed peers, but neurocognitive performance starts to fall behind that of HIV-unexposed children during childhood ( Smith et al, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…For instance, deficits in semantic fluency performance might indicate difficulties in planning, monitoring and decision making. Furthermore, because previous research indicates that working memory scores predict reading and math achievement [ 33 ] these children may under‐achieve educationally.…”
Section: Discussionmentioning
confidence: 99%